Imagine the next generation: Multiple voices on childhood experience from Turkey - HACIFAZLIOĞLU, ÖZGE; TORAN, MEHMET (Taylor and Francis Online, 2018)
This study aims to reveal the meanings attached to the concept of childhood and discuss how it is conceptualized and shaped with cultural attributes by parents and preschool teachers. The study was based on both quantitative and qualitative stance. One hundred and thirty parents and 125 preschool teachers participated in the first phase of the study. As a follow-up study, face to face interviews were also conducted with 11 parents and 13 preschool teachers to provide in-depth explanations for the definitions of childhood. Results showed that parents and preschool teachers placed the child as the representative of the moral values as well as emphasizing the obedience as one of the main qualities that a child should have. Their expectancies from their children seem to be in parallel with the meaning they attribute to childhood. Cultural, educational and psychological factors seem to be influential in the ways parents and preschool teachers define childhood.
Keywords: Childhood; Generation; Preschool Teacher; Parent